1980
DOI: 10.1016/0021-9797(80)90570-6
|View full text |Cite
|
Sign up to set email alerts
|

Static light scattering of concentrated silica dispersions in apolar solvents

Abstract: Organophilic silica dispersions, containing spherical monodisperse particles up to concentrations of 80% (w/v) of silica, were studied with the (static) light-scattering method. Cyclohexane and chloroform were chosen as solvents in order to minimize the scattering intensity. The results were interpreted with fluid-state theories. In a large range of silica concentrations the osmotic compressibility as well as the scattering at finite angles could be described rather well with hardsphere interactions. The hard-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…However, Van Helden et al 7 have already reported the presence of carbon in the composition of Stöber silica particles. They assumed that the carbon content determined gravimetrically originates from unhydrolyzed ethoxy groups and calculated that the particles contain 91.5% weight silica, 5.25% water and 0.97% ethoxy groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Van Helden et al 7 have already reported the presence of carbon in the composition of Stöber silica particles. They assumed that the carbon content determined gravimetrically originates from unhydrolyzed ethoxy groups and calculated that the particles contain 91.5% weight silica, 5.25% water and 0.97% ethoxy groups.…”
Section: Discussionmentioning
confidence: 99%
“…They carried out a systematic study of the reaction parameters and after some major changes of the experimental conditions he has obtained suspensions of quasi-monodisperse silica spheres. After this pioneering work, Stöber silica particles have been used as model colloids in a large number of experimental *e-mail: fernagal@iqm.unicamp.br investigations [7][8][9][10] . Based on the Stöber method, Kaiser 11 prepared completely porous silica particles by co-hydrolysis and subsequent condensation of tetraethoxysilane and an n-alkyltrialkoxysilane in a mixture of ethanol, water and aqueous ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…At moderate pH, these anions provide a long-range electrostatic repulsive interaction between individual particles. In order to neutralize the surface charge for studies of short-ranged interactions, these charges can be removed by surface esterification (22,24,(32)(33)(34).…”
Section: Silica Particlesmentioning
confidence: 99%
“…This formalism has been successfully implemented in the analysis of light scattering [8], small angle X-ray (SAXS) [9] d an small angle neutron scattering (SANS) [lo] on dispersions of colloidal particles with steep short ranged repulsive interactions [ll].…”
Section: Introductionmentioning
confidence: 99%